Microfluidic microbial fuel cells and their applications: a review - Riazul Raziq (2016)
Microfluidic Microbial Fuel Cells, μMFCs, are miniaturized versions of microbial fuel cells, MFCs, which have the capability to generate clean electricity from any biodegradable substance. Many configurations of μMFCs exist. μMFCs may or may not contain mediators and may or may not contain cation-specific membranes. More electricity may be produced by μMFCs compared to MFCs primarily because of their high surface area to volume ratio. μMFCs practically can neither be used for wastewater treatment, nor desalination, but they can be used to rapidly optimize conditions and materials needed for MFCs with high throughput. This paper describes what μMFCs are and how they can be used apart from generating electricity. μMFCs can be applied as power supply to heart pacemakers and as implantable self-sufficient in-vivo glucose sensors that can generate their own energy.